Optimizing The Competitiveness of Return on MudhÃ¢rabah Time Deposit in Improving Public Interest to Invest in Islamic Bank - Syaparuddin Razak (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
The aim of this study is to explain the calculation of return on mudhÃ¢rabah time deposit for the depositors of Islamic banks, and the provision of a fair return to the depositors without leaving any shariah elements. These two issues have become urgent to be discussed in this study, because if their money is deposited in Islamic banks, it will increase the amount of funds available in the Islamic bank, and the amount of funds available directly influence the size of the investment return on Islamic banks. If the results of the large investment, the returns will be obtained by the depositors are also large, and vice versa. In addition, it will also create a sense of calm and peace for themselves, because the money they have deposited in Islamic bank is not only quaranteed by the gorverment but also the system is run in accordance with the shariah of Islam.